Reviewers’ Identity Cues in Online Product Reviews and Consumers’ Purchase Intention - Li, Ji; Liang, Xv (Frontiers in Psychology, 2022)
This research performs three experiments to investigate the influence mechanisms of identity cues in product reviews on consumers’ purchase intention, and to examine the effects of reference groups. The results indicate that: (1) identity cues in positive reviews have a significant positive impact on consumers’ purchase intention, while identity cues in negative reviews have a significant negative impact on consumers’ purchase intention; in addition, identity cues play a greater role in amplifying the impact of negative reviews on purchase intention; (2) emotional social support has a mediating role in the relationship between reviewers’ identity cues and purchase intention, while informational social support and review credibility only play significant mediating roles under all positive reviews scenario; and (3) identity cues of dissociative groups have a negative impact on purchase intention, whereas identity cues of in-groups or aspirational groups have a positive impact on the purchase intention. These findings complement existing research on online reviews and offer insights into the management and strategic oversight of product reviews for e-commerce platforms and merchants.